The last empire : thirty years of Portuguese decolonization - Lloyd-Jones, Stewart; Pinto, António Costa (Intellect, 2003)
This book is the result of a conference organised by the Contemporary Portuguese Political History Research Centre (CPHRC) and the University of Dundee that took place during September 2000. The purpose of this conference, and the resulting book, was to bring together various experts in the field to analyse and debate the process of Portuguese decolonisation, which was then 25 years old, and the effects of this on the Portuguese themselves. For over one century, the Portuguese state had defined its foreign policy on the basis of its vast empire & endash; this was the root of its 'Atlanticist' v.